2021
DOI: 10.3390/ph14121266
|View full text |Cite
|
Sign up to set email alerts
|

An Explanation for the Adiponectin Paradox

Abstract: The adipokine adiponectin improves insulin sensitivity. Functional signal transduction of adiponectin requires at least one of the receptors AdipoR1 or AdipoR2, but additionally the glycosyl phosphatidylinositol-anchored molecule, T-cadherin. Overnutrition causes a reduction in adiponectin synthesis and an increase in the circulating levels of the enzyme glycosyl phosphatidylinositol-phospholipase D (GPI-PLD). GPI-PLD promotes the hydrolysis of T-cadherin. The functional consequence of T-cadherin hydrolysis is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 86 publications
1
17
1
Order By: Relevance
“…Not all adipokines stimulate tumor growth; in fact, adiponectin (Acrp30) is an important adipokine with anti-inflammatory and beneficial metabolic effects, and is a protein hormone with 244 amino acids that signals through three distinct receptors, AdipoR1 and AdipoR2 (expressed in several organs, tissues, and cell lines) and a third receptor protein, T-cadherin (a receptor mainly expressed in the vascular system). Acrp30 exists as oligomers with low (LMW), medium (MMW), and high molecular weights (HMW), the latter form having the most important biological effects [77]. Several datasets support the hypothesis of both direct and indirect roles for Acrp30 as a regulatory mediator of various mechanisms underlying lung carcinogenesis.…”
Section: Adiponectin and Lung Cancermentioning
confidence: 85%
“…Not all adipokines stimulate tumor growth; in fact, adiponectin (Acrp30) is an important adipokine with anti-inflammatory and beneficial metabolic effects, and is a protein hormone with 244 amino acids that signals through three distinct receptors, AdipoR1 and AdipoR2 (expressed in several organs, tissues, and cell lines) and a third receptor protein, T-cadherin (a receptor mainly expressed in the vascular system). Acrp30 exists as oligomers with low (LMW), medium (MMW), and high molecular weights (HMW), the latter form having the most important biological effects [77]. Several datasets support the hypothesis of both direct and indirect roles for Acrp30 as a regulatory mediator of various mechanisms underlying lung carcinogenesis.…”
Section: Adiponectin and Lung Cancermentioning
confidence: 85%
“…Noteworthy, when our manuscript was close to its final layout, a new plausible explanation for 'adiponectin parodox' was proposed by Hans O. Kalkman in his review article in December 2021 issue of Pharmaceuticals [233]. [97], any dysfunction in the system can further aggravate impaired signaling, including the insulin resistance.…”
Section: Facets Of Adiponectin Paradoxmentioning
confidence: 88%
“…[97], any dysfunction in the system can further aggravate impaired signaling, including the insulin resistance. In such circumstances metformin, acting on adiponectin pathway and inducing AMPK activation downstream of adiponectin receptors, can be a therapy of choice [233].…”
Section: Facets Of Adiponectin Paradoxmentioning
confidence: 99%
“…On the other hand, different studies have observed that high levels of this adipokine are associated with a higher risk of death, including CVR. Hence, it is sometimes called the “adiponectin paradox” [ 109 ]. Menon et al showed that an increase in serum adiponectin among stages 3–4 of CKD by 1 µg/mL was associated with a 6% higher CVR [ 110 ].…”
Section: Adipokines and Their Influence On Pathogenesis Nutritional D...mentioning
confidence: 99%